Head and neck cancer radiotherapy amid COVID‐19 pandemic: Report from Milan, Italy. Issue 7 (18th June 2020) - Alterio, Daniela; Volpe, Stefania; Marvaso, Giulia; Turturici, Irene; Ferrari, Annamaria; Leonardi, Maria Cristina; Lazzari, Roberta; Fiore, Massimo Sarra; Bufi, Giammaria; Cattani, Federica; Arrobbio, Camilla; Patti, Filippo; et al.
Abstract: Background: Management of head and neck cancers (HNC) in radiation oncology in the coronavirus disease 2019 (COVID‐19) era is challenging. Aim of our work is to report organization strategies at a radiation therapy (RT) department in the first European area experiencing the COVID‐19 pandemic. Methods: We focused on (a) dedicated procedures for HNC, (b) RT scheduling, and (c) health care professionals' protection applied during the COVID‐19 breakdown (from March 1, 2020 to April 30, 2020). Results: Applied procedures are reported and discussed. Forty‐three patients were treated. Image‐guided, intensity modulated RT was performed in all cases. Median overall treatment time was 50 (interquartile range: 47‐54.25) days. RT was interrupted/delayed in seven patients (16%) for suspected COVID‐19 infection. Two health professionals managing HNC patients were proven as COVID‐19 positive. Conclusion: Adequate and well‐timed organization allowed for the optimization of HNC patients balancing at the best of our possibilities patients' care and personnel's safety.